In vitro effects of acetylcholinesterase reactivators on monoamine oxidase activity - Fišar, Zdeněk; Hroudová, Jana; Korábečný, Jan; Musílek, Kamil; Kuča, Kamil (Toxicology letters, 2011)
Administration of acetylcholinesterase (AChE) reactivators (oximes) is usually used in order to counteract the poisoning effects of nerve agents. The possibility was suggested that oximes may show some therapeutic and/or adverse effects through their action in central nervous system. There are no sufficient data about interaction of oximes with monoaminergic neurotransmitter's systems in the brain. Oxime-type AChE reactivators pralidoxime, obidoxime, trimedoxime, methoxime and HI-6 were tested for their potential to affect the activity of monoamine oxidase of type A (MAO-A) and type B (MAO-B) in crude mitochondrial fraction of pig brains. The compounds were found to inhibit fully MAO-A with half maximal inhibitory concentration (IC(50)) of 0.375 mmol/l (pralidoxime), 1.53 mmol/l (HI-6), 2.31 mmol/l (methoxime), 2.42 mmol/l (obidoxime) and 4.98 mmol/l (trimedoxime). Activity of MAO-B was fully inhibited by HI-6 and pralidoxime only with IC(50) 4.81 mmol/l and 11.01 mmol/l, respectively. Methoxime, obidoxime and trimedoxime displayed non-monotonic concentration dependent effect on MAO-B activity. Because oximes concentrations effective for MAO inhibition could not be achieved in vivo at the cerebral level, we suppose that oximes investigated do not interfere with brain MAO at therapeutically relevant concentrations.
Keywords: Monoamine Oxidase; Animals; Monoamine Oxidase Inhibitors; oximy; Pyridinium Compounds; pyridinové sloučeniny; Pralidoxime Compounds; prasata; trimedoxim; mozek; monoaminoxidasa; pralidoximové sloučeniny; Oximes; Trimedoxime; Obidoxime Chloride; inhibitory MAO; Brain; Swine; reaktivátory cholinesterasy; obidoxim chlorid; zvířata; Cholinesterase Reactivators